Implementation of Animated Videos to Improve the Science Learning Outcomes of Junior High School Students - Nabila, Athaya Safa; Widiansyah, Arindra Trisna (Science Education and Application Journal, 2025)
In the digital era, the use of animated videos is necessary as a learning medium because it presents visual and audio forms without the need for direct observation. This study specifically focuses on improving learning outcomes in science subjects. This classroom action research was conducted in two cycles following Kemmis and Taggart’s model (1988). The research subjects involved were 24 seventh-grade students from SMP NU Miftakhul Jannah because the learning resources available at the school are not yet varied. Data were collected through observation and tests. Quantitative data analysis shows an increase from cycle I to cycle II from 58.24% to 83.2 %. These findings suggest that animated videos can serve as an effective tool for improving student learning outcomes, particularly in technology-integrated education.